2011
DOI: 10.3892/ol.2011.357
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Hedgehog signaling molecules and its involvement in triple-negative breast cancer

Abstract: Abstract. The purpose of this study was to investigate the activation of Hedgehog (Hh) signaling molecules and its involvement in triple-negative breast cancer (TNBC). A total of 123 cases of paraffin blocks, including 83 cases of primary breast carcinoma, 30 cases of mammary hyperplasia and 10 cases of normal breast tissue, were immunohistochemically analyzed for Sonic Hedgehog (SHH), Patched-1 (PTCH1), Smoothened (SMO) and glioma-associated oncogene homoglog 1 (GLI1) expression. The expression of SMO and GLI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 33 publications
3
47
0
Order By: Relevance
“…SMOH encoding of a transmembrane protein acting in a receptor complex was affected by PTCH-1 15,16,18,23. Tao et al studied patients having triple-negative breast cancer by immunohistochemical analysis of factors in the SHH pathway 26. They observed that expression of PTCH-1 was significantly decreased in breast cancer compared with mammary hyperplasia.…”
Section: Discussionmentioning
confidence: 99%
“…SMOH encoding of a transmembrane protein acting in a receptor complex was affected by PTCH-1 15,16,18,23. Tao et al studied patients having triple-negative breast cancer by immunohistochemical analysis of factors in the SHH pathway 26. They observed that expression of PTCH-1 was significantly decreased in breast cancer compared with mammary hyperplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Further evidence for differing Hh patterns within the different breast cancer subgroups was illustrated by the finding of Gli-1 and Smo overexpression in TN breast cancer cases and a positive correlation with increased tumor stage. This was offset by an inverse correlation with estrogen receptor (ER) expression, again suggesting subtype-specific expression patterns [ 36 ]. In vitro studies of Gli-1 have shown high levels of expression in SUM145 cells, which are basal type B as well as triple negative, yet it was not increased in other triple negative and basal-like breast cancer lines, including MDA-MB-231.…”
Section: Hedgehog-signaling Pathway In Breast Cancermentioning
confidence: 99%
“…Thus, suggesting that other factors contribute to high Gli-1 expression in these cells [ 32 ]. On the other hand Gli-1 expression was lower in the ER-positive breast cancer cell lines T47D and MCF7 [ 36 ]. Studies of Gli-1 in vivo report increased expression in four out of five paired normal and tumor clinical samples, which was not statistically significant, which could be due to small sample size [ 45 ].…”
Section: Hedgehog-signaling Pathway In Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…In one such study [126], it was observed that Gli1 expression correlated well with basal breast cancer subtype, and the patients with high nuclear expression of Gli1 had significantly reduced survival time. In another study that focused on triple negative breast cancers [127], it was observed that Smoothened and Gli1 were significantly upregulated in triple negative breast cancers, as compared to the other breast cancer subtypes. The individual members of hedgehog signaling, Shh, Gli1, and Smoothened, were found to correlate with increased metastasis and tumor grade while, at the same time, Gli1 expression was inversely associated with ER.…”
Section: Molecular Factors That Influence Breast Cancer Recurrencementioning
confidence: 99%